Oxygenated hemoglobin as prognostic marker among patients with systemic sclerosis screened for pulmonary hypertension - Xanthouli, Panagiota; Gordjani, Ojan; Benjamin, Nicola; Trudzinski, Franziska; Egenlauf, Benjamin; Harutyunova, Satenik; Marra, Alberto M.; Milde, Nicklas; Nagel, Christian; Blank, Norbert; Lorenz, Hanns-Martin; Grünig, Ekkehard; et al. (Scientific reports, 2023)
Oxygenated hemoglobin (OxyHem) in arterial blood may reflect disease severity in patients with systemic sclerosis (SSc). The aim of this study was to analyze the predictive value of OxyHem in SSc patients screened for pulmonary hypertension (PH). OxyHem (g/dl) was measured by multiplying the concentration of hemoglobin with fractional oxygen saturation in arterialized capillary blood. Prognostic power was compared with known prognostic parameters in SSc using uni- and multivariable analysis. A total of 280 SSc patients were screened, 267 were included in the analysis. No signs of pulmonary vascular disease were found in 126 patients, while 141 patients presented with mean pulmonary arterial pressure ≥ 21 mmHg. Interstitial lung disease (ILD) was identified in 70 patients. Low OxyHem ≤ 12.5 g/dl at baseline was significantly associated with worse survival (P = 0.046). In the multivariable analysis presence of ILD, age ≥ 60 years and diffusion capacity for carbon monoxide (DLCO) ≤ 65% were negatively associated with survival. The combination of low DLCO and low OxyHem at baseline could predict PH at baseline (sensitivity 76.1%). This study detected for the first time OxyHem ≤ 12.5 g/dl as a prognostic predictor in SSc patients. Further studies are needed to confirm these results.